GFR estimation in nephrotic patients: creatinine and/or cystatin-C based equations, or none of them? - Fabiola Carrara; Serenella Valaperta; Mariagrazia Alessio; Matias Trillini; Alessia Gennarini; Aura Crispino; Alessandro Villa; Tobia Peracchi; Daniela Cugini; Nadia Stucchi; Ilaria Pagani; Giuseppe Remuzzi; et al. (Clinical Kidney Journal, 2026)
Abstract Background The performance of serum creatinine and/or cystatin-c-based CKD-Epidemiology (CKD-Epi) Collaboration and European-Kidney-Function-Consortium (EKFC) GFR estimates (eGFRcr, eGFRcys and eGFRcr + cys, respectively) in nephrotic patients with CKD is unknown. Methods We retrospectively evaluated the performance of all the six aforementioned equations in 100 blood samples collected one-year apart from 50 consenting patients with primary Membranous Nephropathy (MN) and proteinuria > 3.5 g/24-h who had their GFR simultaneously measured with the iohexol plasma clearance technique during three intervention studies. The study had > 85% power to detect a significant difference between actual and reference (0.90) concordance correlation coefficient (CCC). Results With CKD-Epi and EKFC, eGFRcr values overestimated, whereas eGFRcys values underestimated (P < 0.001 for all) mGFR. eGFRcr + cys bias was significant (P < 0.05) in hypo-albuminemic participants. Biases significantly increased with worsening hypoalbuminemia, but independently of proteinuria. In normo-albuminemic participants, CCC did not differ from the 0.90 reference value and total deviation index (TDI) was < 30 only with CKD Epi and EKFC eGFRcr + cys equations. The error exceeded 10% in > 40% of estimates. Over one year, mGFR increased by 4.8 ml/min/1.73m2 (P = 0.008). This change was not captured by any equation. Conclusions The performance of GFR estimation equations is acceptable only when creatinine and cystatin-c are simultaneously used as filtration markers in nephrotic patients without hypoalbuminemia. Direct GFR measurement is needed for accurate kidney function evaluation in those with hypoalbuminemia, and whenever individual clinical decision makings (including dosing of toxic medications with renal clearance) or evaluations of treatment effects on GFR changes over time are needed in clinics or research.